End-of-Life and Palliative Care Issues for Patients Living with Pulmonary Arterial Hypertension: Barriers and Opportunities - Ali, Hyeon-Ju; Sahay, Sandeep (Seminars in Respiratory and Critical Care Medicine, 2023)
Pulmonary arterial hypertension (PAH) is a progressive, incurable disease that results in significant symptom burden, health care utilization, and eventually premature death. Despite the advancements made in treatment and management strategies, survival has remained poor. End-of-life care is a challenging issue in management of PAH, especially when patients are in younger age group. End-of-life care revolves around symptom palliation and reducing psychosocial disease burden for a dying patient and entails advanced care planning that are often challenging. Thus, support from palliative care specialist becomes extremely important in these patients. Early introduction to palliative care in patients with high symptom burden and psychosocial suffering is suggested. Despite of the benefits of an early intervention, palliative care remains underutilized in patients with PAH, and this significantly raises issues around end-of-life care in PAH. In this review, we will discuss the opportunities offered and the existing barriers in addressing high symptom burden and end-of-life care issues. We will focus on the current evidence, identify areas for future research, and provide a call-to-action for better guidance to PAH specialists in making timely, appropriate interventions that can help mitigate end-of-life care issues.
Keywords: pulmonary arterial hypertension; palliative care; end-of-life; utilization; barriers